2020
DOI: 10.1177/1932296820928067
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Accelerating Insulin on an Artificial Pancreas System Without Meal Announcement: An In Silico Examination

Abstract: Background: Controlling postprandial blood glucose without the benefit of an appropriately sized premeal insulin bolus has been challenging given the delays in absorption and action of subcutaneously injected insulin during conventional and artificial pancreas (AP) system diabetes treatment. We aim to understand the impact of accelerating insulin and increasing aggressiveness of the AP controller as potential solutions to address the postprandial hyperglycemia challenge posed by unannounced meals through a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Managing unannounced meals could go through algorithmic refinements such as analysing the patient’s hourly meal probability, 21 but also through the usage of new, short-acting insulin analogs. 22…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Managing unannounced meals could go through algorithmic refinements such as analysing the patient’s hourly meal probability, 21 but also through the usage of new, short-acting insulin analogs. 22…”
Section: Discussionmentioning
confidence: 99%
“…Managing unannounced meals could go through algorithmic refinements such as analysing the patient's hourly meal probability, 21 but also through the usage of new, short-acting insulin analogs. 22 Finally, it is worth mentioning that our Virtual Patient Simulator is neither certified nor validated by a notified body. Therefore the simulation results presented throughout this paper should be taken with care.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, from a control design standpoint, using a commercial hybrid AID system is somehow limiting, since the core algorithm should remain unaltered, leaving only room for changes to user-defined profiles (CR, CF, and BR) that the controller uses to command insulin. For instance, in the work of Colmegna et al, 15 it is shown that having the freedom to change the cost function of an model predictive control (MPC)-based AID allows to match glycemic performances between hybrid and fully automated approaches when insulin is accelerated. To the best of the authors’ knowledge, the only previous works where the control strategy was explicitly adapted to the new insulin type were presented in the works of Lachal et al 16 and Russell et al, 17 showing that adaptation increases differences in favor of the faster analogue.…”
Section: Discussionmentioning
confidence: 99%
“…The idea of adjusting the control strategy when switching to faster analogues was explored by our group in a previous work, 15 where the controller's aggressiveness was adapted to changes in the insulin PK profile. Similarly, in the work of Lachal et al, 16 performance of the Diabeloop DBLG1 system was tested in an in-house virtual patient simulator with and without adaptation to the insulin type.…”
Section: Introductionmentioning
confidence: 99%
“…The 10-15 min onset action delay in subcutaneously-administered rapid-acting insulin formulations greatly restricts the controller performance against unannounced meals. Lee et al (2013) and Colmegna et al (2021b) show in silico that insulins with faster absorption improve performance against unannounced meals for PID and MPC control, respectively, without resorting to ad-hoc methodologies like in Section 2.3.1. Two alternatives enable more rapid insulin absorption: ultra-fast-acting insulin formulation and the intraperitoneal route for insulin administration.…”
Section: Accelerating Insulin Absorptionmentioning
confidence: 99%